Friedel's salt formation in sulfoaluminate cements: A combined XRD and 27Al MAS NMR study. (January 2015) - Paul, G.; Boccaleri, E.; Buzzi, L.; Canonico, F.; Gastaldi, D.
Abstract: Four different binders based on calcium sulfoaluminate cements have been submitted to accelerated chlorination through ionic exchange on hydrated pastes, in order to investigate their ability to chemically bind chloride ions that might reduce chloride penetration. The composition of hydrated cements before and after the treatment was evaluated by means of an X-Ray Diffraction– 27 Al Magic Angle Spinning Nuclear Magnetic Resonance Spectroscopy combined study, allowing to take into account even partially amorphous phases and to make quantitative assumption on the relative abundance of the different aluminium-containing phases. It was found that low SO3 Sulfoaluminate–Portland ternary systems are the most effective in binding chloride ions and the active role played by different members of the AFm family in chloride uptake was confirmed. Moreover, a peculiar behavior related to the formation of Friedel's salt in different pH conditions was also established for the different cements.